2014
DOI: 10.1650/condor-14-54.1
|View full text |Cite
|
Sign up to set email alerts
|

Low neutral genetic diversity in isolated Greater Sage-Grouse (Centrocercus urophasianus) populations in northwest Wyoming

Abstract: Identifying small, isolated populations is a conservation priority, not only because isolation may result in negative fitness consequences, but these populations may also harbor unique genetic diversity. The Greater Sage-Grouse (Centrocercus urophasianus) is a widespread obligate species of the sagebrush biome in western North America that has experienced range-wide contraction over the past century. To prevent local extirpation, efforts have been made to identify isolated populations. Here, we analyzed 16 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
2
12
0
Order By: Relevance
“…Similarly, there was a correlation between conditional genetic distance and geographic distance. These results support prior findings of isolation by distance across the species’ range (Bush et al., ; Cross et al., ; Davis, Reese, Gardner, & Bird, ; Fedy, Row, & Oyler‐McCance, ; Oyler‐McCance, Taylor, & Quinn, ; Schulwitz, Bedrosian, & Johnson, ). However, nodes with greater centrality, important to both local and network‐wide genetic exchange, are located across the species’ range.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, there was a correlation between conditional genetic distance and geographic distance. These results support prior findings of isolation by distance across the species’ range (Bush et al., ; Cross et al., ; Davis, Reese, Gardner, & Bird, ; Fedy, Row, & Oyler‐McCance, ; Oyler‐McCance, Taylor, & Quinn, ; Schulwitz, Bedrosian, & Johnson, ). However, nodes with greater centrality, important to both local and network‐wide genetic exchange, are located across the species’ range.…”
Section: Discussionsupporting
confidence: 89%
“…Schulwitz et al. () found that the subpopulations in southern and southeastern Montana and the Dakotas were both highly connected to leks in northern Wyoming. We also found the same pattern of connectivity, evident in the hub‐and‐spoke topology of the minimum spanning tree.…”
Section: Discussionmentioning
confidence: 99%
“…Oyler-McCance et al 2005a, Bush et al 2011, Schulwitz et al 2014, the Bi-State population(Oyler-McCance et al 2014), and Gunnison Sage-Grouse(Oyler-McCance et al 2005b). Even so, clustering of individuals within the Gunnison Sage-Grouse and the Bi-State groups in this study (Figure 3) are evident and are consistent with previous microsatellite data.…”
supporting
confidence: 92%
“…Johnson et al (2010) emphasized the importance of managing populations according to their specific population dynamics and not assuming that the same management will be optimal across a species. The small, isolated San Miguel population represents unique genetic diversity for Gunnison Sage-Grouse (Oyler-McCance et al 2005), which similarly has been found for isolated populations of Greater SageGrouse (Schulwitz et al 2014, Davis et al 2015c, OylerMcCance et al 2015. These genetic differences may be related to different processes exhibited by the different populations, and highlight the need to preserve the genetic diversity that is present in isolated populations.…”
Section: Discussionmentioning
confidence: 64%